Factors associated with the Single Leg Squat test in female soccer players: a cross-sectional study - Ressman, J.; von Rosen, P.; Grooten, W. J. A.; Rasmussen-Barr, E. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background The Single Leg Squat (SLS) test is widely used in the clinical setting to examine and evaluate rehabilitation goals. It is simple to perform and is proposed to have biomechanical and neuromuscular similarities to athletic movements. The aim of the present study was to investigate whether demographics, previous injuries, and biomechanical and psychosocial factors are associated with the outcome of the SLS, assessed as a total score for all segments and as a separate knee segment in elite and sub-elite female soccer players.